Modele pomocy misjom na podstawie działalności Fundacji Pomocy Humanitarnej „Redemptoris Missio” w perspektywie 25 lat (1992-2017) w świetle dokumentacji źródłowej oraz jej periodyków - Wrzos, Marcin (Annales Missiologici Posnanienses, 2023)
The Poznań Foundation of Humanitarian Relief “Redemptoris Missio” originated twenty-five years ago. Its mission is to provide professional medical assistance to missionaries and mission centers. It is the first foundation which involved lay people in the missionary activity of the Catholic Church. It was also founded mostly by lay people and is still managed by them. Many lay volunteers are also engaged in its work. In this study the author describes the genesis of the Foundation and its goals in the context of the pastoral paradigm. The analytical-critical method of its functioning was analyzed, as well as analysis of the source documents of the foundation. On the basis of the foundation's activities an institutional model of secular involvement in the Church’s missionary activity is presented, which can be replicated in other pastoral centers.